BDNF, GDNF, NGF and Klotho levels and neurocognitive functions in acute term of schizophrenia - Betul Aslan Turkmen; Esra Yazici; Derya Guzel Erdogan; Mehmet Akif Suda; Ahmet Bulent Yazici (BMC Psychiatry, 2021)
Abstract Background Klotho and its relationship with neurotrophic factors and cognition in schizophrenia has not yet been investigated. In this study, the hypothesis that the blood serum levels of BDNF, GDNF, NGF and Klotho in schizophrenia patients and healthy controls would be related to cognitive functions was investigated. Methods In this study, two groups were assessed: schizophrenia patients (case group) who were hospitalised in the Psychiatry Clinic of Sakarya University Training and Research Hospital and healthy volunteers (control group). The patients were evaluated on the 1st and 20th days of their hospitalisation with the Positive and Negative Syndrome Scale (PANSS), the Brief Psychiatric Rating Scale (BPRS), the General Assessment of Functioning Scale (GAF) and the Clinical Global Impression Scale (CGI). For cognitive assessment, both groups were evaluated with the Wechsler Memory Scale-Visual Production Subtest (Wechsler Memory Scale III-Visual Reproduction Subtest) and the Stroop test. Results BDNF, GDNF, NGF and Klotho levels were lower in schizophrenia patients than in healthy controls. In the schizophrenia patients, on the 20th day of treatment, there was a statistically significant increase in BDNF compared to the 1st day of treatment. BDNF, GDNF and Klotho showed positive correlations with some cognitive functions in the healthy controls. BDNF, GDNF, NGF and Klotho levels were intercorrelated and predictive of each other in both groups. Conclusion This study suggests a relationship between cognitive functions, neurotrophic factors and Klotho. Most of the results are the first of their kind in the extant literature, while other results are either similar to or divergent from those generated in previous studies. Therefore, new, enhanced studies are needed to clarify the role of Klotho and neurotrophic factors in schizophrenia.